Preliminary phytochemical screening, analysis of phenolic compounds and antioxidant activity of Genista cephalantha Spach. (Fabaceae) - Chebbah Kaoutar,; Marchioni Eric,; Menad Ahmed,; Mekkiou Ratiba,; Sarri Djamel,; Ameddah Souad,; Boumaza Ouahiba,; Seghiri Ramdane,; Benayache Samir,; Benayache Fadila, (International Journal of Phytomedicine, 2014)
This study was designed to estabilish a preliminary phytochemical screening, evaluate the phenolic and flavonoid content according to the Folin-Ciocalteu procedure, and aluminum chloride method respectively and to determine qualitatively, using HPLC-UV method, the most important products present in ethyl acetate (EtOAc) and n-butanol (n-BuOH) extracts of the aerial parts of Genista cephalantha Spach. from east Algeria. The antioxidant activity of these extracts was spectrophotometrically tested by measuring their ability to scavenge a stable DPPH free radical and by β-Carotene/linoleic acid bleaching assay. Evaluated extracts showed a good activity in both antioxidant system assays.